Association between genetic clades and cancer prevalence suggested by French-wide study of oncogenic small ruminant β-retrovirus diversity - Riocreux-Verney, Benjamin; Verneret, Marie; Diesler, Rémi; Dolmazon, Christine; Gineys, Barbara; Cadoré, Jean-Luc; Turpin, Jocelyn; Leroux, Caroline (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionENTV (Enzootic Nasal Tumor Virus) and JSRV (Jaagsiekte Sheep Retrovirus) are β-retroviruses responsible for respiratory cancers in sheep and goats. In this study, we analyzed the genetic features of the sheep and goat β-Retroviruses (29 JSRV and 24 ENTV strains) circulating in France to identify molecular signatures associated with disease severity in flocks.MethodsWe developed a highly specific PCR to amplify and sequence exogenous targeted regions or near full length proviruses based on limited discriminating motifs along their genomes.ResultsThe phylogenetic reconstructions based on the Long Terminal Repeat (LTR) and env regions suggest that one major strain is circulating on the French territory for ENTV-1 and ENTV-2 while not clustering with already published Spanish, Canadian or Chinese strains. JSRV strains circulating in French sheep flocks were distributed in 2 distinct genetic clades clustering with sequences originating from North America, Africa and United-Kingdom. JSRV clade I was found to be associated with a higher incidence of cancer in French flocks. Specific motifs spanning the entire JSRV genome particularly in the LTRs and in the intracytoplasmic domain of the envelope were detected between the two genetic subtypes.DiscussionThis work represents the first nationwide study describing the circulation of the three closely related β-oncogenic retroviruses JSRV, ENTV-1 and ENTV-2 in French sheep and goat flocks. Better characterization of strain genetics is a critical step in monitoring circulating - retroviruses, especially those associated with higher cancer incidence in small ruminants.